Inflammation, infection and depression: an evolutionary perspective. (9th December 2019) - Doyle, Caroline; Swain, Walker A.; Swain Ewald, Holly A.; Ewald, Paul W.
Abstract: Abstract: The evolutionary basis for clinical depression is not well understood. A growing body of literature that is not based on evolutionary logic links inflammation to depression. Integration of these findings with an evolutionary framework for depression, however, needs to address the reasons why the body's inflammatory response would be regulated so poorly that it would result in incapacitating depression. Pathogen induction of inflammation offers an explanation, but the extent to which the association between inflammation and depression can be attributed to general inflammation as opposed to particular effects of pro-inflammatory pathogens remains unclear. This paper reports a study of sexually transmitted pathogens, which addresses this issue. Although several sexually transmitted pathogens were associated with depression according to bivariate tests, only Chlamydia trachomatis and Trichomonas vaginalis were significantly associated with depression by a multivariate analysis that accounted for correlations among the pathogens. This finding is consistent with the hypothesis that infection may contribute to depression through induction of tryptophan restriction, and a consequent depletion of serotonin. It reinforces the idea that some depression may be caused by specific pathogens in specific evolutionary arms races with their human host.